2018
DOI: 10.1103/physrevb.97.014501
|View full text |Cite
|
Sign up to set email alerts
|

Noncentrosymmetric superconductor BeAu

Abstract: Mixed spin-singlet and spin-triplet pairing can occur in noncentrosymmetric superconductors. In this respect, a comprehensive characterization of the noncentrosymmetric superconductor BeAu was carried out. It was established that BeAu undergoes a structural phase transition from a low-temperature noncentrosymmetric FeSi structure type to a high-temperature centrosymmetric structure in the CsCl type at T-s = 860 K. The low-temperature modification exhibits a superconducting transition below T-c = 3.3 K. The val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
55
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(72 citation statements)
references
References 68 publications
14
55
2
1
Order By: Relevance
“…27,28 However, a more comprehensive analysis of the superconducting state in Y 4 Be 33 Pt 16 is currently underway. In particular, because several in-depth muon spin-rotation, relaxation, and resonance experiments performed on another Be-containing non-centrosymmetric superconductor BeAu 24 revealed that not only type-I character, 29 but also a multi-gap nature of superconductivity 30 may exist in such unconventional systems.…”
Section: Resultsmentioning
confidence: 99%
“…27,28 However, a more comprehensive analysis of the superconducting state in Y 4 Be 33 Pt 16 is currently underway. In particular, because several in-depth muon spin-rotation, relaxation, and resonance experiments performed on another Be-containing non-centrosymmetric superconductor BeAu 24 revealed that not only type-I character, 29 but also a multi-gap nature of superconductivity 30 may exist in such unconventional systems.…”
Section: Resultsmentioning
confidence: 99%
“…After melting, the boule was annealed in an argon atmosphere for 48 hours at 400 • C. Further details can be found in Ref. [30].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The data of Cu 0.09 Bi 2 Se 3 were extracted from our magnetization measurement, and other data points of Cu x Bi 2 Se 3 were obtained from magnetization and μSR measurements in previous reports [53,55]. [143], Nb 0.5 Os 0.5 [114], Re 6 Zr [144], Mo 3 P [113], and BeAu [145], thin films of transition-metal nitrides NbN [14,91], heavy fermions superconductors UPt 2 , UBe 13 and Ce 1−x Yb x CoIn 5 [146][147][148], and conventional metal superconductors [82,119].…”
Section: Discussionmentioning
confidence: 99%